PENGARUH CORPORATE GOVERNANCE TERHADAP MANAJEMEN PAJAK (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2018)
This research aims to explain about an influence of corporate governance to tax management. Tax management was measured by effective tax rate, whereas corporate governance was shown by variable, such as size of commissioner, percentage of independent commissioner, institutional ownership, managerial ownership, and audit committee. A sample of this study consists of companies which are listed in wholesale trade sector, retail trade sector, tourism, restaurant, and hotel sector during the year 2014 to 2016. Determination of the sample chosen from purposive sampling method and accomplished a sample of 33 companies based on certain criteria. The data are collected from Indonesia Stock Exchange and used Eviews 8 to analyse multiple regression. The result showed that size of commissioner, percentage of independent commissioner, managerial ownership has influence on tax management. Based on this research, institutional ownership and audit committee has no influence on tax management.Keywords: corporate governance, tax management, effective tax rate